2012
DOI: 10.1007/s11325-012-0765-4
|View full text |Cite
|
Sign up to set email alerts
|

Forces created by mandibular advancement devices in OSAS patients

Abstract: The force values recorded in this study may explain the occlusal and skeletal side effects associated with long-term use of these oral appliances. They illustrate the influence of the extent of mandibular advancement, and indicate a possible dose-dependent effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 45 publications
2
23
0
1
Order By: Relevance
“…29 It has been previously shown that the relationship between the force applied to the arches and amount of mandibular advancement is almost linear, with the force increasing with increasing mandibular advancement. 24 In the present study, patients with a greater amount of initial overjet tended to see larger total reductions to both overjet and overbite. This may be due to the greater amount of clearance for the forward movement of the lower dentition that occurs in these patients, before the lower anterior teeth would contact the corresponding upper anterior teeth.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…29 It has been previously shown that the relationship between the force applied to the arches and amount of mandibular advancement is almost linear, with the force increasing with increasing mandibular advancement. 24 In the present study, patients with a greater amount of initial overjet tended to see larger total reductions to both overjet and overbite. This may be due to the greater amount of clearance for the forward movement of the lower dentition that occurs in these patients, before the lower anterior teeth would contact the corresponding upper anterior teeth.…”
Section: Discussionsupporting
confidence: 44%
“…The force required to suspended the mandible and associated soft tissues thus is transmitted to the dental arches and likely results in the occlusal changes reported. 24 It should be understood then that the dental side effects of MAS treatment are a product of protruding the mandible to achieve a therapeutic effect rather than specific appliance design. 25 This is likely why studies examining side effects comparing different appliance designs have found very little difference in terms of magnitude of these secondary effects of dental movement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent in vivo study [30] an almost linear relationship between recorded force and mandibular advancement was found, reaching up to 13.6 N. Forces in this order of magnitude may not only cause potentially irreversible changes of occlusion [30] but may also increase the risk of loss of retention of the MAD. Further research is needed to translate the in vitro forces measured in the present test into clinically relevant indicators and to determine the key design features of MADs explaining the differences in retention characteristics measured.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen-Levy et al used a pressure transducer system with OA in OSA patients and measured forces created by progressive mandibular advancement for each step of 1 mm. They found that the mean force was 1.18 N/mm, which exhibited an almost linear evolution [21]. …”
Section: Discussionmentioning
confidence: 99%